Pengaruh Media Konkret Terhadap Pemahaman Konsep Siswa Dalam Pembelajaran IPA di Sekolah Dasar - Julaska Sari; Feniareny Feniareny; Bambang Hermansah; Mega Prasrihamni (Universitas Negeri Padang, 2023)
This study aims to determine the effect of concrete media on sound material on conceptual understanding. This research was carried out in the odd semester of the 2022/2023 academic year. This research method is a Pre-Experimental method with a research design of One Group Pretest-Posttest Design. The sample of this research is one class which opens 28 students. The research instrument was written in the form of multiple choice as many as 15 questions. Based on the research, the average value of the pretest results of the experimental class was 61.67 and the average value of the posttest results increased to 83.57. So, the increase based on the pretest and posttest scores is 21.9. In addition, through hypothesis testing with t-test results obtained that the value of the statistical table t = 12,325 with df = 27 and the number sig. or p-value of 0.000 <0.05, which means H_0 is rejected. So it can be said that there is a significant effect on understanding science concepts before and before being given concrete media to grade IV-A students at SD Negeri 195 Palembang.